2018
DOI: 10.1016/j.scitotenv.2017.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Sources and geographic origin of particulate matter in urban areas of the Danube macro-region: The cases of Zagreb (Croatia), Budapest (Hungary) and Sofia (Bulgaria)

Abstract: The contribution of main PM pollution sources and their geographic origin in three urban sites of the Danube macro-region (Zagreb, Budapest and Sofia) were determined by combining receptor and Lagrangian models. The source contribution estimates were obtained with the Positive Matrix Factorization (PMF) receptor model and the results were further examined using local wind data and backward trajectories obtained with FLEXPART. Potential Source Contribution Function (PSCF) analysis was applied to identify the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 56 publications
(66 reference statements)
3
20
1
1
Order By: Relevance
“…The concentrations of sulfate, nitrate and ammonium obtained in this study on the coast of Bou Ismaïl and in other areas in the Mediterranean Sea are shown in Table 2. The observed concentrations in this study are lower than those measured in the atmospheres of Marseille (El Haddad et al, 2009), Zagreb (Perrone et al, 2018), Antalya (Ö ztürk et al, 2012), the harbor of Barcelona (Pey et al, 2013), and rural Finakolia in Greece (Li et al, 2013). They are of the same order of magnitude as those recorded at the urban site of Oporto (Custódio et al, 2016).…”
Section: Water-soluble Ions (Wsi)contrasting
confidence: 62%
“…The concentrations of sulfate, nitrate and ammonium obtained in this study on the coast of Bou Ismaïl and in other areas in the Mediterranean Sea are shown in Table 2. The observed concentrations in this study are lower than those measured in the atmospheres of Marseille (El Haddad et al, 2009), Zagreb (Perrone et al, 2018), Antalya (Ö ztürk et al, 2012), the harbor of Barcelona (Pey et al, 2013), and rural Finakolia in Greece (Li et al, 2013). They are of the same order of magnitude as those recorded at the urban site of Oporto (Custódio et al, 2016).…”
Section: Water-soluble Ions (Wsi)contrasting
confidence: 62%
“…Accordingly, they concluded that dust storms enrich the ambient airborne microbiome with new soil-derived bacteria that disappear as the dust settles, suggesting that the bacteria are transported attached to dust particles [30]. Similarly, recent investigations of the desert dust composition suggest that toxic waste may be transported through the movement of desert dust [31][32][33]. Given that environmental regulations between countries from which the dust originates and the countries to which it is transported may significantly differ, this may present a fertile area of research, with a significant impact on public policy and air quality standards [20].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, most research on the health risks of PM has been documented in urban areas where PM emissions are mainly derived from traffic, domestic sources, and industry [5]. Regional, as well as long-range, atmospheric transport also affects PM concentrations in urban areas [6]. While a very active research area, there is, at present, no scientific consensus on differentiated health risks of PM from different sources [7].…”
Section: Introductionmentioning
confidence: 99%